Unsaponifiable fraction isolated from grape (Vitis vinifera L.) seed oil attenuates oxidative and inflammatory responses in human primary monocytes. Issue 4 (17th April 2018) - Millan-Linares, Maria C.; Bermudez, Beatriz; Martin, Maria E.; Muñoz, Ernesto; Abia, Rocio; Millan, Francisco; Muriana, Francisco J. G.; Montserrat-de la Paz, Sergio
Abstract : Grape seed oil has significant potential for the management of inflammatory and oxidative conditions. Abstract : Grape ( Vitis vinifera L.) seed has well-known potential for production of oil as a byproduct of winemaking and is a rich source of bioactive compounds. Herein, we report that the unsaponifiable fraction (UF) isolated from grape seed oil (GSO) possesses anti-oxidative and anti-inflammatory properties towards human primary monocytes. The UF isolated from GSO was phytochemically characterized by GC-MS and HPLC. Freshly obtained human monocytes were used to analyse the effects of GSOUF (10–100 μg mL −1 ) on oxidative and inflammatory responses using FACS analysis, RT-qPCR, and ELISA procedures. GSOUF skewed the monocyte plasticity towards the anti-inflammatory non-classical CD14 + CD16 ++ monocytes and reduced the inflammatory competence of LPS-treated human primary monocytes diminishing TNF-α, IL-1β, and IL-6 gene expression and secretion. In addition, GSOUF showed a strong reactive oxygen species (ROS)-scavenging activity, reducing significantly nitrite levels with a significant decrease in Nos2 gene expression. Our results suggest that the UF isolated from GSO has significant potential for the management of inflammatory and oxidative conditions and offer novel benefits derived from the consumption of GSO in the prevention of inflammation-related diseases.